Learners’ Engagement with Teacher Written Corrective Feedback (WCF) in EFL Context: Associations with Writing Ability - Indyra Mahdiana; Yudhi Arifani; Slamet Asari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Learners’ engagement with written corrective feedback as main part which connects between provision of written corrective feedback and writing outcomes. In other words, the level of learners’ engagement with written corrective feedback will determine learners’ writing ability. This current study completes the existing literatures by examining relationship between learners’ engagement with teacher written corrective feedback and learners’ writing ability. The correlation design was implemented in this research among 88 participants which divided into three classes. Learners were asked to do writing task and revise it based on teacher WCF which they receive. Then, learners also need to fill nine items of learners’ engagement with teacher WCF questionnaire. The results of this research showed that there was very strong positive correlation between learners’ engagement with teacher WCF and learners’ writing ability with the value of pearson correlation was 0.824 and sig. tailed was 0.000 < 0,05. It indicated that the correlation between learners’ engagement with teacher WCF and learners’ writing ability was important and real. So, learners’ engagement with teacher WCF could be used as one of predictor factors of writing ability.